INTERNALIZATION OF DISCIPLINE CHARACTER VALUES IN SCOUTING ACTIVITIES IN MADRASAH IBTIDAIYAH - Ilmi, Siti Nailul; Sutomo, Moh; Muhith, Abd (Program Studi PGMI, 2024)
This research explores the role of scouting activities in shaping the disciplinary character of students at MIMA Nurul Huda Gondang Rejo. Scouting, as a form of non-formal education, plays a crucial role in instilling values such as faithfulness, nobility, law-abidance, and disci-pline in children and young people. The Ministry of Education and Culture mandates scout-ing activities in schools as a combination of attitudinal values and skills development. The study focuses on scouting activities at MIMA Nurul Huda Gondang Rejo, where scouting be-came a compulsory extracurricular activity in 2017. The extracurricular activities are de-signed to not only develop scouting skills but also to build character, emphasizing politeness, obedience, and discipline. The activities include both indoor and outdoor components, providing students with a holistic learning experience. The research methodology employs a descriptive qualitative approach, utilizing observation, interviews, and documentation to gather primary data. The results highlight the achievements of MIMA Nurul Huda Gondang Rejo scouts, including notable successes in various competitions. Scout coaches play a pivot-al role in implementing activities aligned with the 2013 Curriculum, using learning methods that make the experience enjoyable for students. The study also identifies constraints faced by scouts, such as economic limitations affecting the acquisition of complete attributes. Motiva-tion is found to be positively influenced by external coaches. Despite challenges, the research underscores the importance of discipline character education, emphasizing the need for con-tinuous support from coaches and parents. The internalization of discipline character through scouting activities is evident in students' behaviors, including punctuality, adherence to rules, and completion of tasks on time. While students face difficulties, the coaches' role in providing guidance and motivation is crucial. The research concludes that character education at MI-MA Nurul Huda Gondang Rejo effectively shapes disciplined students, emphasizing the collaborative efforts of coaches and students in creating a conducive learning environment.